EXPANSION OF THE VILLAGE FOR IMPROVING EFFICIENCY OF PUBLIC SERVICE - Sudarsana Sudarsana (Universitas Sebelas Maret, 2015)
The research background about the village set out in Law No.32 of 2004 : “village is a legal entity with boundaries whose authority controls and manages the interest of local communities, based on their origin and local customs which are respected by the government system of the Republic of Indonesia”. Considering that the village has the authority to regulate and manage the interests of the community in accordance with the local socio-cultural conditions, the original village autonomy is strategically positioned that requires balanced attention to the implementation of regional autonomy because strong village autonomy will significantly affect the realization of local autonomy. Establishment of a village aims to create effectiveness and efficiency of village governance and improve public services to accelerate the realization of public welfare . Establishment of new village outside existing villages or as a result of village expansion management. Village expansion is splitting a village into two or more villages. The purpose of this study is to investigate and analyze implementation of requirements that must be met in the establishment of new villages in terms of social ,economic, cultural, and legal aspects especially in villages Ketro and Wonosidi, District Tulakan, Pacitan, beside Simultaneously formulating a feasibility recommendation of new village establishment according to social economic, cultural and legal issues in preparation for splitting the village into independent villages especially in villages Ketro and Wonosidi, District Tulakan, Pacitan. The research method, research activities on the potential for rural district expansion as an effort to increase the efficiency of public services in the distric of Pacitan is a descriptive qualitative research and will be supported by the data both quantitative and qualitative (socio economic, cultural and legal aspects). The research is carried out the villages Ketro and Wonosidi, District Tulakan, Pacitan. Research is focused on assessing the requirement variables mechanisms and procedures for the establishment expansion of a new village district that must be met by the provisions of the enforced legislation in terms of socio economic, cultural and legal issues in preparation for the village expansion to independent villages especially villages in Ketro and Wonosidi. Data are collected through observation, interviews, questionnaires, focus groups, and document studies. In order to test the validity of the data, a series of validation is done throught data triangulation and data analysis using interactive analysis, stakeholder analysis, hierarchy process analysis and strength, weakness, opportunity, and threat (SWOT). The results showed that the preparation of village expansion in Ketro and Wonosidi, District Tulakan, Pacitan is done according to the terms of a new village establishment, the village formation mechanisms and procedures for the establishment of the village, infrastructure setting, sociate institution setting, village wealth setting, village boundaries setting and a map of the village, and the village zoning arrangement. The conclusion, based on the requirements, mechanisms and procedures in accordance with Regulation village expansion area Pacitan districs No.4 of 2008, the village Ketro “meet” requirements and deserves to be split into four independent villages, namely, the master village / definitive Ketro named village, while the village expansion / preparation Ketro village named Asri, Sempurejo and Pelemrejo. Meanwhile, Wonosidi village, district, and Tulakan is also eligible and worthy to be split into two independent villages with the main village Wonosari. Effects of the village expansion is the responsibility of the concerned villages and local governments can regulate the expansion of the village in accordance with legislation in force. Keywords : Village Expansion Potential, efforts to improve public service efficiency.